2003
DOI: 10.1177/000992280304200304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Supplementation on Catch-Up Growth in Picky Eaters

Abstract: Ninety-two subjects ages 36 to 60 months who had picky-eater behavior and evidence of growth faltering were randomized to receive either nutrition counseling alone, or nutrition counseling plus a nutritional supplement (Study) for 90 days. The Study group had significantly greater increases in weight and height. There were no significant differences between groups in changes in appetite or activity levels, or in gastrointestinal symptom scores. The percent of subjects who developed upper respiratory tract infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 25 publications
2
65
0
6
Order By: Relevance
“…A comparison of five different studies referenced on a commercially-sponsored website [34] provides a case study [35,36,37,38,39]. Collectively, these studies provided a concentrated liquid supplement (1 kcal/mL; 12% protein, 44% carbohydrate, 44% fat) and are cited to support the statement “clinically proven nutrition to help kids grow” [34].…”
Section: The Scientific Rationale For the Claims: The Nature Of Thmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison of five different studies referenced on a commercially-sponsored website [34] provides a case study [35,36,37,38,39]. Collectively, these studies provided a concentrated liquid supplement (1 kcal/mL; 12% protein, 44% carbohydrate, 44% fat) and are cited to support the statement “clinically proven nutrition to help kids grow” [34].…”
Section: The Scientific Rationale For the Claims: The Nature Of Thmentioning
confidence: 99%
“…Ninety-two “picky eaters” aged 3 to 5 years with “evidence of growth faltering” were randomized to receive either nutrition counseling alone, or nutrition counseling plus the nutritional supplement for 90 days [36]. The latter group gained more weight and height than the unsupplemented, counseled group.…”
Section: The Scientific Rationale For the Claims: The Nature Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…This trial showed greater increases in growth parameters in children who received ONS plus dietary counselling compared with those who received only dietary counselling. 6 Another recent study demonstrated that ONS with dietary counselling improved nutrient adequacy in young Chinese children with picky eating behaviour and with weight-for-height below the 25th percentile. 16 In a 48-week nutritional intervention study, provision of ONS combined with dietary counselling promoted catch-up growth in weight and improved linear growth during the growth maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
“…We could identify only two trials in children published in peer reviewed journals. One trial described favourable short-term increases in weight and height for children taking HEOS aged >3 years in Taiwan and the Philippines 1. However, a trial in the UK of HEOS use in children with cystic fibrosis did not show any difference in body mass index (BMI) in the treated group 2…”
Section: Introductionmentioning
confidence: 99%